Multiple concentric rainbows induced by microscale concave interfaces for reflective displays. (September 2021) - Rada, Jacob; Hu, Haifeng; Zhou, Lyu; Zeng, Jing; Song, Haomin; Zeng, Xie; Shimul, Shakil; Fan, Wen; Zhan, Qiwen; Li, Wei; Wu, Limin; Gan, Qiaoqiang
Abstract: In our current world, active display technology creates a glut of energy demand to meet its illumination needs. This demand can be stymied by using reflective display technologies that require no active illumination, with some examples including: electronic paper using electrophoretic motion of ink particles, electrowetting of water/oil droplets, and interferometric modulators, all of which have been commercialized. However, due to the lack of active light sources, it is difficult to implement these reflective display technologies in low light environments (e.g. nighttime display). In this work, we report an experimental observation of multiple concentric circular rainbows from reflective microscale concave interfaces (MCIs), which are introduced by the reflection of optical rays within a polymer-embedded microsphere. Exit rays from a single edge and opposite edges will introduce completely different interference mechanisms depending on the illumination and observation conditions, which will result in different angle-dependent colors. By clarifying the mechanism behind this coloration phenomenon, as well as quantitatively mapping the generated color, the implementation of the MCI in smart signs and pixelated displays are demonstrated, showing angle-dependent color-changing reflected images that can be observed over a wide spatial angle range. This structural material will serve as a building block for the development of new platforms for light-matter interactions, on-chip sensors, anti-counterfeiting tools, and passive and smart color reflective displays. Intriguingly, we also demonstrate a smart MCI traffic sign for both visible and infrared wavelengths that will introduce extra signals for pattern and image recognition in order to enhance the safety of future autopilot/autonomous systems. Graphical abstract: Image, graphical abstract